أثر استراتيجية شجرة المشكلات في تحصيل مادة اللغة العربية لدى طلاب الصف الرابع الادبي (Journal of the College of Basic Education, 2024)
The current research aims to identify (the effect of the problem tree strategy on the acquisition of the Arabic language subject among fourth grade literary students) The researcher followed the experimental method, as it is the appropriate and suitable method for the nature of his research and its goal. The researcher defined the current research population as second-grade intermediate students in the government middle and secondary schools for boys affiliated with the Baghdad/Al-Karkh First Directorate of Education in the academic year (3202-4202), then determined the research sample consisting of Of (69) students in Al-Radwaniyah Preparatory School for Boys, distributed into two groups, the experimental group includes (35) students, and the control group includes (34) students.The researcher taught the same two research groups, and the experiment lasted for a full semester. The researcher formulated (76) behavioral objectives and the researcher prepared (14) model teaching plans, including (7) plans for teaching using the (problem tree) strategy, (7) plans for teaching in the usual way, and presented a model of two plans. Two teaching sessions were presented to a group of arbitrators in the field of the Arabic language, its teaching methods, and its teachers. In light of their opinions and suggestions, some amendments were made and it took its final form.The researcher studied the two research groups himself, and the teaching period lasted (10) weeks, and the experiment ended with the application of the achievement test consisting of (40) items with (34) objective multiple-choice items and (6) short-answer essay items after the researcher made sure of its veracity and accuracy. The discriminatory power of its paragraphs, the difficulty factor, the effectiveness of the wrong alternatives, and its stability. The researcher used the following statistical methods: the Smirnov test, the Levene test, and the t-test for two independent samples, the item difficulty factor, the discrimination factor, the effectiveness of false alternatives, the Cronbach alpha equation, and the effect size equation. After analyzing the data, the researcher arrived at the following: The experimental group that studied according to the (problem tree) strategy outperformed the control group that studied according to the usual method.